(untitled) (The Pakistan Development Review, 2015)
I would like to thank the organisers and the PIDE for giving me the honour to present this year’s Allama Iqbal Lecture on the subject of Child Poverty and Economic Growth and the opportunity to talk to such well-informed and distinguished audience. I believe that child poverty and economic growth is a subject that is rarely discussed but I think it is a crucial subject for the 21st century. I have only got a brief time to talk to you, so I will only be able to skim over the surface of many issues. If you want to go into a greater depth, there is a website for the Townsend Centre for International Poverty Research, where you can find more details about the issues to which I am going to talk.